Berlitz Japanese CD pack (Singapore Berlitz / APA, 2002)
This CD pack features Japanese dialogues with over 300 essential expressions. The phrase book contains more than 1,200 useful words and phrases, travel tips, dictionary and pronunciation guide.
"Berlitz Japanese CD pack with phrase book"--Container.
Compact disc.
Keywords: Japanese language -- Self-instruction.; Japanese language -- English. -- Conversation and phrase books